Resilience as meaning-making: Adolescents’ experiences of cyberbullying in post-conflict Ambon, Indonesia – a qualitative narrative study - Nur Setiawati Dewi; Roland Lekatompessy (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Research on cyberbullying has largely focused on psychological outcomes and individual coping strategies, with limited attention to how adolescents narratively construct resilience within specific cultural and historical contexts. In post-conflict societies, adolescents’ responses to cyberbullying are shaped not only by personal resources but also by moral expectations, spiritual discourses, and power-laden digital environments. Objective: This study aimed to explore how adolescents in post-conflict Ambon, Indonesia, narratively construct resilience through their meaning-making of cyberbullying experiences. Methods: A qualitative narrative inquiry design was employed. Participants were recruited using purposive sampling through senior high schools, universities, and youth community networks in urban and semi-urban areas of Ambon, Maluku Province, Indonesia. In-depth narrative interviews were conducted in 2021 with twelve adolescents aged 16–19 years who reported experiences of cyberbullying. Data were analyzed drawing on Riessman’s approach to narrative analysis, focusing on the connections and recurring patterns across narratives through which resilience was articulated and meaning was constructed, rather than treating narratives as linear or unified trajectories. The study was reported in accordance with the Consolidated Criteria for Reporting Qualitative Research (COREQ). Results: Five narrative threads were identified through which adolescents narrated resilience in the context of cyberbullying. These narratives did not follow a single or linear pathway but reflected emotional wounding, silence as an ambivalent form of endurance, spiritually mediated meaning-making under constraint, moral restraint as identity negotiation, and tentative efforts to reclaim self-worth through compassion and reframing. Silence and spirituality functioned as culturally shaped resources that at times provided moral coherence or protection, while simultaneously revealing despair, constraint, and limited perceived options within morally regulated and digitally surveilled environments. Conclusion: Adolescents’ resilience to cyberbullying in post-conflict Ambon was narrated not as recovery or empowerment, but as an ongoing and culturally embedded process of endurance, moral negotiation, and partial re-authoring of self-worth. For nursing practice, these findings underscore the importance of narrative-sensitive and culturally responsive approaches that attend to adolescents’ silence, spiritual expressions, and moral frameworks, while fostering safe spaces for meaning-making and psychosocial care.